Impact of social prescribing to address loneliness: A mixed methods evaluation of a national social prescribing programme. (20th October 2020) - Foster, Alexis; Thompson, Jill; Holding, Eleanor; Ariss, Steve; Mukuria, Clara; Jacques, Richard; Akparido, Robert; Haywood, Annette
Abstract: Loneliness is considered a global public health issue because of its detrimental impact on physical and mental health but little is known about which interventions can reduce loneliness. One potential intervention is social prescribing, where a link worker helps service‐users to access appropriate support such as community activities and social groups. Some qualitative studies have identified that social prescribing may help to reduce service‐users' loneliness. Given this, the British Red Cross (a third sector organisation) developed and delivered a national social prescribing service in the United Kingdom to support people who were experiencing, or at risk of, loneliness. Service‐users could receive up to 12 weeks of support from a link worker. A mixed methods study was conducted to understand the impact of the support on loneliness, and to identify the facilitators and barriers to service delivery. The study included: (a) analysis of quantitative data collected routinely between May 2017 and December 2019 ( n  = 10, 643) including pre‐post analysis of UCLA data ( n  = 2, 250) and matched comparator work to measure changes in loneliness; (b) semi‐structured interviews with service‐users, link workers and volunteers ( n  = 60) and (c) a Social Return on Investment Analysis. The majority of the service‐users (72.6%, n  = 1634/2250) felt less lonely after receiving support. The mean change in UCLA score was −1.84 (95% CI −1.91 to −1.77) of a maximum change of 6.00 (decrease indicates an improvement). Additional benefits included improved wellbeing, increased confidence and life having more purpose. The base case analysis estimated a social return on investment of £3.42 per £1 invested in the service. Having skilled link workers and support tailored to individual needs appeared key. However, challenges included utilising volunteers, meeting some service‐users' needs in relation to signposting and sustaining improvements in loneliness. Nonetheless, the service appeared successful in supporting service‐users experiencing loneliness.